New onset, transient and stable motoric cognitive risk syndrome: Clinical characteristics and association with incidence of probable dementia in the NuAge cohort - Beauchet, Olivier; Matskiv, Jacqueline; Gaudreau, Pierrette; Allali, Gilles (Frontiers in Aging Neuroscience, 2023)
Background. Motoric cognitive risk syndrome (MCR) is a pre-dementia stage. The existence of stable and transient MCR, their related clinical characteristics and their association with incident dementia is a matter of debate. Objective. This study aims to examine the clinical characteristics and the time course associated with new onset, transient and stable MCR, and their association with incidence of probable dementia in community-dwelling older adults living in the province of Quebec (Canada). Design. Quebec elderly population-based observational cohort study with three years of follow-up. Setting. Community dwellers. Subjects. A subset of participants (n=1,113) from the “Quebec Longitudinal Study on Nutrition and Successful Aging” (NuAge) cohort. Methods. Participants with MCR were identified at baseline and after 1 year of follow-up. Socio-demographic characteristics, 30-item Geriatric depression scale (GDS) score, cardiovascular risk factors and diseases were recorded at baseline. Incidence of probable dementia was measured at annual follow-up visits over a 3-year period. Results. Over the period of the first year of follow-up, the prevalence of MCR was 8.5% with 4.3% having new onset MCR, 2.8% transient MCR and 1.4% stable MCR. A higher 30-item GDS score was reported with new onset and transient MCR, and the highest prevalence of cerebrovascular diseases was shown with stable MCR compared to non-MCR participants (P<0.05). MCR was associated with overall incidence of probable dementia, regardless of its status (Hazard Ratio >1.86, P≤0.034). Conclusion. Greater prevalence of depressive symptoms and cerebrovascular diseases were reported respectively with new onset and transient MCR, and stable MCR. The association of MCR with incidence of probable dementia remains significant, regardless of MCR subtypes.